Potential Invasive Pests of Agricultural Crops - Peña, Jorge E (CABI, 2014)
Numbers of exotic pests and the damage that they inflict to agricultural crops and ecosystems are increasing all over the world because of expanding international transport, tourism, global climate change and trade in agricultural products (Kiritani, 2001; Yan et al., 2001). While inherent arthropod pest dispersion has resulted in invasion of foreign habitats, we humans have been responsible for trade and transportation of alien species for millennia (Hulme, 2009). According to Pimentel et al. (2005) c. 50,000 alien-invasive species are estimated to have been introduced into the USA. Of these, 4500 species are arthropods (Pimentel et al., 2005). According to CSIR (2009), California acquires on average six invasive species each year. In Florida, 271 insect species were reported as new arrivals between 1971 and 1991 (Frank and McCoy, 1993), while Hawai’i and Florida are thought at present to acquire new species at a rate of c. 15 species per annum (CSIR, 2009). While a significant number of pests come from different parts of the world, Central and South America and the Caribbean region appear to be the major sources of pests intercepted in the USA (McCullough et al., 2006). Miami is by far the most important port of interceptions with c. 117,498 insects and 2800 mites intercepted between 1984 and 2000 (McCullough et al., 2006). While the orders Hemiptera, Lepidoptera and Diptera collectively account for >75% of insect interceptions into the USA, Coleoptera, Heteroptera and Lepidoptera had the highest species diversity of intercepted insects (McCullough et al., 2006). In Europe, 57 species from North America and 52 from Asia have established populations in European forests (Mattson et al., 2007). According to Jacas (Josep A. Jacas, Castelló, Spain, pers. comm.) c. 84 new arthropod pests have been introduced into Spain during the period 1965–2010. Of these, 55% are Hemipterans, 10% are Lepidopterans and 14% are mites. The importance of invasive Hemipterans in South-East Asia and West Africa is documented by Muniappan et al. (2009), and includes the mealybugs Paracoccus marginatus Williams and Granara de Willink, Phenacoccus madeiren- sis Green, P. manihotii Matile-Ferrero, P. solenopsis Tinsley, P. jackbeardsleyi Gimpel and Miller and the whitefly Aleurodicus dugesii Cockerell. The most invasive arthropod species in China include two lepi- dopterans, the banana moth Opogona sacchari (Bojer) and the fall webworm Hyphantria cunea Drury, the cotton mealybug P. solenopsis (a threat to cotton), the Colorado potato beetle Leptinotarsa decem- lineata Say, and a predicted threat to apple of >US$600 million by Cydia pomonella (L.) (Yan et al., 2001; Runzhi et al. (2010a, b, c). In contrast, Richardson et al. (2009) consider that alien insects have caused little (if any) disruption to ecosystems in South Africa. However, it is accepted that for most countries, invasions or introductions of arthropod pests are currently affecting not only ecosystems but also agricultural crops.